2022
DOI: 10.1007/s11468-022-01719-3
|View full text |Cite
|
Sign up to set email alerts
|

Refractive Index Sensor Based on Surface Plasmon Resonance Excitation in a D-Shaped Optical Fiber Coated by Tantalum

Abstract: In this paper, a plasmonic refractive index sensor using a D-shaped optical fiber coated by tantalum has been proposed. The interaction between fiber fundamental mode and plasmonic mode which lead to the formation of resonance peaks depending on the analyte refractive index (RI) are investigated in detail. Using spectral sensitivity methods, the sensing performance of the proposed sensor for detecting analytes is numerically studied. The effect of various design parameters of proposed sensor are optimized nume… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…18 Ta is a metallic dopant that attracts signicant attention because of its distinct surface plasmon resonance band, which allows Ta to function as a photosensitizer, enhancing the optical absorption of materials. 19 The radii of Ta 5+ (0.64 Å), Ta 4+ (0.68 Å), and Ta 3+ (0.72 Å) ions are similar to the radius of Zn 2+ ion (0.74 Å). Therefore, Ta ions have the potential to effectively substitute Zn 2+ in the lattice structure.…”
Section: Introductionmentioning
confidence: 83%
“…18 Ta is a metallic dopant that attracts signicant attention because of its distinct surface plasmon resonance band, which allows Ta to function as a photosensitizer, enhancing the optical absorption of materials. 19 The radii of Ta 5+ (0.64 Å), Ta 4+ (0.68 Å), and Ta 3+ (0.72 Å) ions are similar to the radius of Zn 2+ ion (0.74 Å). Therefore, Ta ions have the potential to effectively substitute Zn 2+ in the lattice structure.…”
Section: Introductionmentioning
confidence: 83%
“…In addition to these materials, several researchers reported achieving an improved sensing response using tantalum dioxide (Ta 2 O 5 ) [123][124][125]. Recently, Das et al reported sensitivity enhancement of a Ta 2 O 5 -coated photonic crystal fiber (PCF)-based glucose sensor [126].…”
Section: Spr Devices Based On Dielectric Materialsmentioning
confidence: 99%
“…294,295 It typically consists of a dielectric or metallic film with subwavelength thickness artificial nanostructures. Furthermore, plasmonic devices can be designed in various ways in terms of multi-materials, complex geometries, and the combination of both, which enable a variety of functions such as optical filters, 296 refractive index sensors, 297 and re-configurable absorbers. 298 After the analyte material is added or spread across the functionalized surface, the interaction affects the overall spectrum to realize the applications in communications, 299 solar cells, 300 gas sensors, 301 biological and chemical related sensors 302 among many other fields.…”
Section: Sensing Strategies (1) Colorimetric-based Detectionmentioning
confidence: 99%